2017
DOI: 10.3390/foods6020016
|View full text |Cite
|
Sign up to set email alerts
|

Can the Palatability of Healthy, Satiety-Promoting Foods Increase with Repeated Exposure during Weight Loss?

Abstract: Repeated exposure to sugary, fatty, and salty foods often enhances their appeal. However, it is unknown if exposure influences learned palatability of foods typically promoted as part of a healthy diet. We tested whether the palatability of pulse containing foods provided during a weight loss intervention which were particularly high in fiber and low in energy density would increase with repeated exposure. At weeks 0, 3, and 6, participants (n = 42; body mass index (BMI) 31.2 ± 4.3 kg/m2) were given a test bat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 53 publications
1
14
0
Order By: Relevance
“…Adequate intake of fat acts as a source of energy enhances the absorption of fat-soluble vitamins, and it is an essential component of the cell membrane and certain hormones [ 64 ]. Moreover, fat improves the palatability of foods [ 65 ]. The WHO recommended that less than 30% of the daily energy must be from fat [ 66 ].…”
Section: Discussionmentioning
confidence: 99%
“…Adequate intake of fat acts as a source of energy enhances the absorption of fat-soluble vitamins, and it is an essential component of the cell membrane and certain hormones [ 64 ]. Moreover, fat improves the palatability of foods [ 65 ]. The WHO recommended that less than 30% of the daily energy must be from fat [ 66 ].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, methods to increase the liking of low-ED foods, in particular fruits and vegetables, have the potential to encourage preferential intake of these foods in the presence of large portions. Such methods include increasing the palatability of low-ED options (4042) as well as repeated exposure to these foods (43, 44). Furthermore, this study and previous work have shown that serving larger portions can be used strategically to increase intake of healthful low-ED foods if they are well-liked (45) and relatively more palatable than the other foods available (18).…”
Section: Discussionmentioning
confidence: 99%
“…These values are similar to those found by a consumer acceptance panel for lentil-fortified soups and casserole dishes which ranged from 5.0 to 7.0 [ 18 ]. Clinical trial interventions consisting of a variety of food types containing a variety of pulse types were scored from 6.4 to 7.5 on a 9-point scale from 1—extremely unpleasant to 9—extremely pleasant [ 26 ]. These ratings are somewhat similar to those found in the current study.…”
Section: Resultsmentioning
confidence: 99%